PENINGKATAN PENGUASAAN KOSAKATA BAHASA INDONESIA PADA MATERI SINONIM DAN ANTONIM MELALUI MEDIA WORDWALL DI KELAS V UPT SDN 064974 KECAMATAN MEDAN TEMBUNG - Ismi Aulia; Hotma Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on field findings indicating that students' ability to master synonyms and antonyms remains weak, as evidenced by their obtained values falling below the Minimum Compliance Criteria (KKM). The goal of this study is to assist students in enhancing their mastery of Indonesian vocabulary by using synonymous and antonymic materials, which cThis research was conducted as part of a class action study in class V SD. tion research conducted in class V SD. The results of this research show that the implementation of learning using wall media can improve student learning outcomes. Based on the conclusion, (1) Teachers can use wordwall as an alternative to improve the mastery of Indonesian vocabulary synonymous and antonym materials students, and (2) Teachers are expected to be able to choose appropriate and interesting media, so that can motivate students to more enthusiastically follow learning in class